Stauroneis kingstonii sp. nov. (Bacillariophyta: Naviculales), a new diatom species from the Black Swamp, Arkansas, USA - Burge, David R. L.; Marsico, Travis D.; Edlund, Mark B. (Phytotaxa, 2015)
A freshwater diatom species, Stauroneis kingstonii sp. nov., is described from cypress-tupelo wetlands of the Cache River, Arkansas, USA. Stauroneis kingstonii can be distinguished from other Stauroneis species by its narrow lanceolate shape, high length:breadth ratio, coarse areolae and striae, and lateral raphe bounded by a broad axial area and straight proximal raphe ends. The diatom is currently known only from the Cache River Watershed and found living benthic or epiphytic on submerged bald cypress and water tupelo tree bark, in slightly acidic, and fresh to slightly brackish waters.